MATERI NILAI SASTRA PROFETIK DALAM KUMPULAN CERPEN RUSMI INGIN PULANG KARYA AHMAD TOHARI - Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2017)
Prophetic literature is a literature involved in the history of humanity, which is transcendental and Sufism spirit as it departs from the values of the world. Prophetic literature aspires to humans not to be one-dimensional creatures, but complete creatures, both physical and spiritual, are rooted in the earth as well as reaching the sky. Therefore the processing of the material is not separated from experience, imagination, and value. One of literary works that include Prophetic literature is a collection of short stories by Ahmad Tohari. To process the value material in the collection Rusmi Ingin Pulang short story writer uses the basis of the verses in various letters in the Qur'an, the Prophet's traditions, the minds of Ki Hajar Dewantara, and R.A.Kartini. The scattering of these values is symbolically utilized to convey the mindset of patience, honesty, forgiveness, affection, wisdom, mutual assistance, science, and self-reliance.